The Effect of Using Canva on Students’ Motivation in Learning English - Tiara Andhini; Iis Sujarwati; Kasmaini Kasmaini (Journal of English Education Program (JEEP), 2026)
Motivation is essential for learning English. But in some cases, student motivation declines, which impacts their learning outcomes. There are many ways to increase this motivation, including using engaging learning media, such as Canva. Therefore, this study aims to determine whether the use of Canva is related to students' motivation to learn English. The sample comprised 46 seventh-semester students in the English Education study program at the University of Bengkulu in the 2025/2026 academic year. The method used in this study was a quantitative correlational analysis using Spearman's rank correlation. The results showed a very strong positive correlation (r=0.813) with a significance level of <0.001. It can be said that the more frequently Canva is used as a learning medium, the higher students' motivation to learn English is. This is because Canva has an attractive, easy-to-use interface that increases students' motivation, participation, and self-confidence. Based on the research results, Canva as a learning medium is important and effective for increasing motivation to learn English at the tertiary level.